Implementation of an Alternative Dispute Resolution for the Banjar Indigenous Community on Credit Agreements in South Kalimantan - Yudhistira, Dhieno; Fajarina, Mentari (International Asia Of Law and Money Laundering (IAML), 2024)
Implementation of ADR dispute resolution for Banjar Indigenous Peoples regarding Credit Agreements in South Kalimantan, the resolution of a dispute is basically always resolved through public courts, whether civil lawsuits or simple lawsuits, in every credit agreement entered into by Banjar Indigenous Peoples in Kalimantan. South, for this reason a new legal problem arises if the legal settlement is taken through the Alternative Dispute Resolution (ADR) route. First: how to execute the credit agreement if using the Alternative Dispute Resolution (ADR) route. Second: how to process the agreement dispute resolution. This credit can be resolved through mediation or arbitration outside of court, especially in South Kalimantan. The method used is a type of normative legal research that is prescriptive in nature. Then regarding the research approach, the author uses a conceptual approach and a statutory approach. The legal material collection technique used is the document study or literature study technique. This research uses the syllogism deduction analysis technique which stems from the submission of a major premise and a minor premise. The major premise is the conclusion of a legal rule, while the minor premise is a legal fact that can be found. Then from these two premises a conclusion or conclusion can be drawn. The results of the research and discussion are that the implementation of Alternative Dispute Resolution in South Kalimantan cannot be separated from article 130 HIR/154 Rbg which provides the legal basis for the existence of mediation institutions in court, but apart from that ADR can also be carried out outside the court with the agreement of the parties to the dispute through preventive and repressive channels by means of prevention through the stages of prudence, supervision and through the stages of mediation, conciliation and arbitration at institutions that have been accredited by the Supreme Court in the form of replacing the dispute resolution clause in the agreement through the courts into the form of dispute resolution through the Alternative Dispute Resolution route with mediation and arbitration methods. A legal bond or relationship between the debtor (debt) and the creditor (debt giver) which regulates the rights and obligations of both parties in South Kalimantan Province. This agreement is usually accompanied by a "guarantee guarantee" (individual) agreement. As in a credit agreement, there is always collateral before making credit.